2019
DOI: 10.5539/ies.v12n8p1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Problematic Internet Use, Sense of Belonging and Social Appearance Anxiety in Facebook Use Intensity of University Students

Abstract: The aim of this study was to examine the role of problematic internet usa, sense of belonging and social appearance anxiety in facebook use intensity of university students. The sample of the study consisted of 484 (332 female, 68.6% and 152 male 31.4%) different faculties of various universities of Konya. Problematic Internet Use Scale, General Belongingness Scale, Facebook Intensity Scale, The Social Appearance Anxiety Scale, Personal Knowledge Form were used in the study. Pearson Correlation Product Conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
(49 reference statements)
0
8
0
1
Order By: Relevance
“…Today, applications in online environments have become an indispensable part of our lives. This situation has brought many negativities such as smartphone addiction, cyberbullying, internet addiction, intense social media use, and digital game addiction (Bakioğlu, 2020;Peker, 2019;Savcı & Aysan, 2017;Savcı et al, 2020;Savcı et al, 2021;Traş et al, 2019). Internet and social media use is common among university students.…”
Section: Discussionmentioning
confidence: 99%
“…Today, applications in online environments have become an indispensable part of our lives. This situation has brought many negativities such as smartphone addiction, cyberbullying, internet addiction, intense social media use, and digital game addiction (Bakioğlu, 2020;Peker, 2019;Savcı & Aysan, 2017;Savcı et al, 2020;Savcı et al, 2021;Traş et al, 2019). Internet and social media use is common among university students.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the effects of the general development characteristics of adolescence on the individual (Arisoy, 2009;Cunningham, Gulliver, Farrer, Bennett, & Carron-Arthur, 2014;Ögel, 2014;Machado, Bruck, Cat, Soares, & Silva, 2018) focuses more attention on internet addiction, which is described as a kind of behavior problem and causes the formation of various psychological symptoms (Arisoy, 2009;Caplan, 2006;Çetin & Ceyhan, 2014;Ögel, 2014;McCord, Rodebaugh, & Levinson, 2014;Machado et al, 2018;Vries, Nakamae, Fukui, Denys, & Narumoto, 2018;Tahiroğlu, Çelik, Bahali, & Avci, 2010). When the literature is analyzed in the literature, it is stated that internet use triggers a high level of emotional loneliness in individuals (Odaci & Kalkan, 2010) and low rates of positive emotions (Koç, 2017); shyness in adolescents (Ayas, 2012), loneliness (Batigün & Hasta, 2010;Esen & Siyez, 2011;Ümmet & Ekşi, 2016), anxiety (Evren, Dalbudak, Evren, & Çiftçi-Demirci, 2014;Jie et al, 2014) recently fear of missing developments in social settings , state of violence (Yayan, Suna-Dağ, & Düken, 2019), social appearance anxiety (Tras, Öztemel, & Baltaci, 2019), depression (Cheung, Chan, Lui, Tsui, & Chan, 2018), attempted suicide (Chang et al, 2015) There are studies showing that Also in other studies; sitting disorders, contractions and eye disorders in adolescents (Akbulut, 2013) insomnia, intense loss of will that occurs with the meaninglessness of life (Nalwa & Anand, 2003), extreme fatigue (Lam, Peng, Mai, & Jing, 2009), eating problems (Canan, 2016), weakening of the immune system (Cao & Su, 2006), mental disorders (Kratzer ...…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the study conducted by Doğan and Çolak, (2016), a significant positive relationship was found between social media use and social appearance anxiety. In addition, studies have found that there is a significant negative relationship between social appearance satisfaction and problematic internet use (Koronczai & et al, 2013;Korkmaz, 2017;Ayar, Özalp-Gercer, Özdemir, & Bektaş, 2018;Tras, Öztemel, & Baltaci, 2019).…”
Section: Discussionmentioning
confidence: 99%